A novel 25-ferroptosis-related gene signature for the prognosis of gliomas - Peng, Xiaojiang; Liu, Chun; Li, Jing; Bao, Zeqing; Huang, Tao; Zeng, Lingfeng; He, Qixiong; Xue, Daojin (Frontiers in Oncology, 2023)
Background: Ferroptosis is closely associated with cancer and great important in immune evasion of cancer. However, the relationship between iron death and glioma is unclear. Methods: We downloaded expression profiles and clinical data of glioma from GlioVis database, and obtained the expression profiles of ferroptosis genes. Ferroptosis related gene signature was developed for the prognosis of the gliomas. Results: We screened out prognostic ferroptosis genes, named ferroptosis-related genes, by Cox regression method. Based on these genes, we used unsupervised clustering to obtain two different clusters; principal component analysis algorithm was applied to determine the genescore of each patient, then all patients were classified into two subgroups. Results showed that there exist obvious differences in survival between different clusters and different genescore subgroups. The prognostic model constructed by 25 ferroptosis-related genes was then evaluated to predict the clinicopathological features of immune activity in gliomas. Conclusion: The ferroptosis-related genes play important role in the malignant process of gliomas, potentially contributing to the development of prognostic stratification and treatment strategies.